Multielemental analysis of thin sections and preliminary interpretations in ceramic fragments from Markaconga- Acomayo Cusco - Bolívar Yapura, Wilber (2021)
The Physicochemical and multielemental analyzes, carried out on ceramic surface fragments from Markaconga, located in the province of Acomayo in Cusco, aimed to determine the relationship and interrelation in the chemical composition of ceramic pastes, pigments and slips present in its decorations, in order to identify moments of manufacture and/or chromatic, symbolic and semiotic transfer, present in these fragments. The same one that allows us to build a preliminary interpretation of the degree of influence and relationships from early societies of the North basin of Lake Titicaca, which had very identifiable stylistic and artistic patterns in their pottery.